Par reduction in OFDM using tone reservation - Hieu, Nguyen Thanh; Kinh, Nguyen Viet (VNU Journal of Science: Natural Sciences and Technology, 2004)
Orthogonal Frequency Division Multiplexing (OFDM) systems support high data rate wireless transmission, offer excellent immunity against fading and intersymbol interference. The major drawback of OFDM is large Peak to Average power Ratio (PAR) of the transmit signals. As consequence, the power amplifier has to be highly linear. Most power amplifiers are non-linear and produce spectral distortion in the adjacent channel of the OFDM-spectrum. There are several methods for reducing the PAR in OFDM systems. This paper investigates Tone Reservation (TR) method of J.Tellado.